Comportamiento agronómico del cultivo de maíz (Zea mays L.) a la aplicación de los fertilizantes edáficos granulares en la zona de Montalvo, Los Ríos - Alarcón Ramírez, Carlos Adonis (2020)
The investigation was carried out on the grounds of the “Don Luis” farm owned by Mr. Luis Duche, “Las Balsas” compound, in the Montalvo canton, Los Ríos province. The planting material was the corn hybrid "Emblema 777", using as treatments the edaphic fertilizers Rafos and Nitrodoble, alone and in mixtures, comparing them against two conventional fertilization programs and a control without application, in three repetitions. The objective of the work was to evaluate the effect of the programs on grain yield. The sowing of corn was carried out manually in experimental units of 20 m2. Treatments were distributed in a randomized complete block design DBCA. The analysis of variance established statistical significance and in the evaluation of means the Tukey test of significance was used at 95%. The variables evaluated were: plant height, insertion height, days to flowering, days to harvest, ear diameter, ear length, grain weight, yield per hectare, agronomic efficiency and economic analysis. The results found establish that all the fertilized treatments surpassed the control without application of fertilizers. The fertilized treatments presented statistical parity in several variables with the exception of days to flowering, days to physiological maturation and grain weight. The Rafos 350 kg/ha + Nitrodoble 120 kg/ha treatment achieved a higher grain yield. The highest agronomic efficiency rate was calculated in the treatment Rafos 250 kg/ha + Nitrodoble 120 kg/ha, with phosphorus being the chemical control and potassium Rafos 250 kg/ha + Nitrodoble 120 kg/ha. Economically, all the treatments were greater than the control. The Raphos + Nitrodoble treatment (350 +120 kg/ha) generated the highest utility